Cadmium exposure induces apoptosis, inflammation and immunosuppression through CYPs activation and antioxidant dysfunction in common carp neutrophils. Issue 99 (April 2020) - Jiaxin, Sun; Shengchen, Wang; Yirong, Cao; Shuting, Wang; Shu, Li
Abstract: Cadmium (Cd) is a bioaccumulative toxic heavy metal element that has been shown to cause irreversible damage to the immune system once contaminated with water, thereby jeopardizing the health of fish and other aquatic organisms. Neutrophils react against multiple invading pathogens through different mechanisms. The effect of Cd immunotoxicity in carp neutrophils has not been thoroughly studied. Here, common carp peripheral blood neutrophils were exposed to 10 μmol/L Cd for 2 h or then stimulated with 20 nmol/L PMA under laboratory conditions to study the effect and potential mechanism of Cd on neutrophils. The results showed that Cd induced mRNA expression of Cytochrome P450s (CYPs) enzymes including CYP1A1, CYP1B1, CYP1C and CYP3A138, increased reactive oxygen species (ROS) levels, and enhanced the expression of antioxidant genes. In addition, Cd activated cysteinyl aspartate specific proteinases (caspase-3) and induced apoptosis by altering the expression of major genes including mitochondrial pathway factors such as B-cell lymphoma-2 (Bcl-2), pro-apoptosis factors Bcl-2-Associated X (BAX), and caspase-9 and death receptor pathways such as Fas/Fas ligand (Fas/FasL), tumour necrosis factor alpha/tumor necrosis factor receptor 1 (TNF-α/TNFR1) and caspase-8. Meanwhile, we found that the accumulation of ROS caused not only oxidative stress but also high expression levels of related inflammatory factors to mediate the immune response including interleukin (IL-6, IL-10, IL-11b, IL-1β) and interferon (IFNg1, IFNph1). Furthermore, Cd also inhibited phorbol myristate acetate (PMA)-induced release of neutrophil extracellular traps (NETs) and respiratory burst. This information will be helpful for the elucidation of how Cd impacts the neutrophils of carp. The associated risk assessment is valuable for effective aquatic environmental management. Graphical abstract: Image 1 Highlights: Cd activates CYPs/ROS pathway in carp neutrophils. Cd causes carp neutrophil apoptosis via mitochondrial and death receptor pathways. Cd exposure induces inflammation of carp neutrophils. Cd inhibits neutrophil extracellular traps formation and respiratory burst.